2019
DOI: 10.1002/jbmr.3854
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screening in a Large Chinese Cohort of Childhood Onset Hypoparathyroidism by Next-Generation Sequencing Combined with TBX1-MLPA

Abstract: At least 15 candidate genes have been implicated in hypoparathyroidism (HP). However, comprehensive screening of causative genes for HP is lacking. Here, we investigated the genotype spectrum in a large group of Chinese patients with childhood onset HP. A total of 173 patients with childhood onset HP were analyzed using targeted next‐generation sequencing (NGS), including 15 candidate genes combined with multiplex ligation‐dependent probe amplification (MLPA) of the TBX1 gene. Twenty‐seven pathogenic or likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
(96 reference statements)
3
20
0
Order By: Relevance
“…revealed in the present study has been previously reported in 14 cases worldwide (Abraham et al, 2017;Grosse et al, 2017;Guo et al, 2014;Isojima et al, 2014;Nikkel et al, 2014;Unger et al, 2013;Wang et al, 2019;Yerawar, Kabde, & Deokar, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…revealed in the present study has been previously reported in 14 cases worldwide (Abraham et al, 2017;Grosse et al, 2017;Guo et al, 2014;Isojima et al, 2014;Nikkel et al, 2014;Unger et al, 2013;Wang et al, 2019;Yerawar, Kabde, & Deokar, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…The variable ID phenotype in KCS1 and SSS has been reported worldwide (Albaramki et al, 2012; Diaz et al, 1999; Haider et al, 2014; Kelly, 2000; Sanjad et al, 1991). The heterozygous de novo c.1706G>A (p.Arg569His) variant in FAM111A revealed in the present study has been previously reported in 14 cases worldwide (Abraham et al, 2017; Grosse et al, 2017; Guo et al, 2014; Isojima et al, 2014; Nikkel et al, 2014; Unger et al, 2013; Wang et al, 2019; Yerawar, Kabde, & Deokar, 2020). None of these patients were described with microcephaly and/or ID, and most were independent studies, with no familial relationship between the patients, except a report on a mother and daughter by Nikkel et al (2014).…”
Section: Discussionsupporting
confidence: 76%
“…In our study, hypoparathyroidism occurred in 92.3% of the patients between the ages of four to 18 years (mean 8.6 ± 3.9 years) and was the first symptom of the triad in about 70% of patients. Previous studies have identified that APS1 accounts for 2.7%–5.2% in childhood-onset patients with hypoparathyroidism [ 9 , 10 ]. Therefore, all childhood-onset patients with hypoparathyroidism should be systematically evaluated for evidence of APS1, and long-term follow-up was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of families with apparently isolated autosomal dominant hearing loss, using NGS panels, revealed that the cause of the deafness was GATA3 mutations and that other previously undetected HDR features were also present (Lin et al, 2015;L. Wang et al, 2017 Wang et al, 2019). In another study, 37 patients with pediatric hypoparathyroidism were sequenced for five candidate genes and GATA3 mutations were identified in 5 patients (Kim et al, 2015).…”
Section: Diagnostic Relevancementioning
confidence: 99%
“…respectively. However, it should be noted that the great majority of patients with isolated hypoparathyroidism or isolated renal dysplasia that were found to have GATA3 mutations, either had incomplete clinical information about other organs or were found to have other features of HDR when examined more closely (e.g., by carrying out formal hearing evaluation) (Hwang et al, 2014;Kim et al, 2015;Sanna-Cherchi et al, 2017;Y. Wang et al, 2019).…”
Section: Diagnostic Relevancementioning
confidence: 99%